Rekayasa Ulang Proses Bisnis Pada Usaha Konveksi Fasco Di Kota Malang - Nashrullah, Aditya; Suharso, Wildan (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Changes in the industrial world are developing very rapidly, with increasingly complex business competition and increasingly broad scope of company operations. Business Process Reengineering (BPR) is a concept that involves deep and drastic restructuring with the aim of achieving process improvements, cost reductions, and increased system speed. The Fasco Convection Business requires system reengineering by finding production management processes and reports that have inefficient processes and times and have never been reengineered for approximately 6 years. Managers must manage the production process by hiring employees directly in the field or by telephone. Managers must also record reports using conventional notebooks until the reports are distributed through report books. The method used in system reengineering is through Business Process Reengineering (BPR). In addition, this study uses the ASME (American Society of Mechanical Engineers) standard to evaluate throughput efficiency and process analysis. In this study, the production management process and reports were obtained which had an efficiency value of 93.24%, but when the reengineering was carried out, thirteen processes were eliminated, eight processes were automated, and four processes remained. In the end, it can reach 100% percentage with a more efficient time of 182 minutes than the previous process.